Algunos aspectos de la bioecología de la cigua Cittarium pica (mollusca: gasteropoda) en el Darién Caribe Colombiano (2012)
ABSTRACT: The bioecology of West Indian topshell (Cittarium pica) was studied in the Colombian Caribbean Darien, sampled monthly for a year at four stations located on the rocky coastline of Capurganá and Sapzurro in the municipality of Acandí. Physicochemical variables were recorded, density and size distribution in the gastropod. Additionally, five individuals were collected to determine the reproductive state, proportion of sexes and minimal sexual maturity size. It was found that the abundance is positively related to the salinity gradient; the average density was 5.4 + 6 individuals/m2. The majority of individuals were classified in the smallest sizes being 79 mm shell width the maximum size. C. pica reproduced continually with a spawning peak in September (wet season). The population showed a normal sex proportion (1:1) and a minimum sexual maturity of 29 mm. The population studied is affected by natural factor such as temporary freshwater inputs. It also presents evidence of overexploitation as they found few individuals of large size. Additionally, in September and October time which present the largest spawning of C. pica, is celebrated The Cigua Festival (a traditional festivity in Capurganá) brings with itself a massive fishing of this snail for consumption and marketing.